Documentary History: Origins, Supports & Ecuadorian Avant-Gardes - Celi, Esteban; Foncseca, Edison (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
This article talks about the Documentary and its beginnings, its process, its classification, the creative process and the elements that make it up, while analysing its history in Ecuador based on important references. It also contains the approach that indicates the concept of technology as a vehicle of the audio-visual avant-gardes. The cinematographic supports, the first discoveries, give rise to the cinema, and to a moment of the art that will tattoo the memory of the masses to the point that the black and white transmits certain information to us, that will be enriched by the other elements of the narratives.